Electrochemical tyrosinase biosensor based on cellulose nanocrystals decorated with CdS quantum dots and Fe₃O₄ nanoparticles for determination of phenol - Abd Manan, Fariza Aina (2018)
Phenolic compounds, including phenol and simple substituted phenols, are among the major hazardous pollutants persistent in industrial effluent that may harm human health and aquatic life. Owing to their toxicity, there are numerous quantitative methods that are implemented for the determination of phenolic compounds based on chromatographic and spectrophotometric analysis. However, these methods are inconvenient for on-site and in situ analysis for field application. Alternatively, enzymatic biosensor has been explored as an excellent devices for determination of phenol in the environment and industrial wastewater. In this research work, two tyrosinase (Tyr) biosensor based on cetyl trimethylammonium bromide funtionalized cellulose nanocrystals (CTAB-CNCs) decorated with mercaptopropionic acidcapped cadmium sulfide quantum dots (MPA-CdS QDs) and mercaptopropionic acid-capped iron oxide (MPA-Fe₃O₄) nanoparticles for determination of phenol was developed. Initially, CTAB-CNCs/MPA-CdS QDs nanocomposite suspension drop coated onto working electrode of SPCE, and dried at room temperature for 3h. The same procedure was applied for the preparation of CTAB-CNCs/MPA-Fe₃O₄ nanocomposite. Next, 7 μL of Tyr were drop casted onto the surface of working electrode consisting CTAB-CNCs/MPA-QDs nanocomposite film. This modified bioelectrode was named as Tyr/CTAB-CNCs/MPA-CdS QDs/SPCE. For comparison, the bioelectrode of Tyr/CTAB-CNCs/MPA-Fe₃O₄/SPCE was also fabricated using the same protocol. In brief, CNCs was chosen as the solid support for enzyme immobilization prior to their special properties of low cytotoxicity, biocompatibility, biodegradability, and environmentally benign. However, CNCs has poor electrical conductivity. Thus, CNCs has been coupled with QDs and Fe₃O₄ to enhance the conductivity. Both QDs and Fe₃O₄ comprises inherent electrochemical properties, cost effectiveness, low toxicity, and environmental friendly and facile synthesis. Hence, the nanocomposites build a synergetic effect for appropriate sensitivity and stability for biosensors. Under the optimal conditions, the Tyr/CTAB-CNCs/MPA-CdS QDs biosensor exhibits good linearity towards phenol in the concentration range of 5 to 40 μM (R2 = 0.985) with sensitivity and limit of detection (LOD) of 0.113 μA/μM and 0.082 μM, respectively. Meanwhile, the Tyr/CTAB-CNCs/MPA-Fe₃O₄ biosensor revealed a good linearity towards phenol concentration ranging from 0.010 to 0.075 μM (R2 = 0.985) with sensitivity and LOD of 32.219 μA/μM and 0.00076 μM, respectively.